A life cycle for creating an uncomplicated software - Dorin, Michael (2019)
Modern software development life cycle models tend to be less formal and less rigid then Waterfall based models of the past. However, creating software without following even the most basic of plans often results in poorly structured, faulty, and hard to maintain software. This paper proposes a practical development model for the purpose for software development. Following some sort of plan produces better code than no plan at all. This model has been shown to be successful even with inexperienced developers.